Evaluasi Kepuasan Mahasiswa terhadap Fasilitas Kampus Menggunakan Metode Simple Additive Weighting (SAW) - Nugroho, Agung Yuliyanto; Tundo, Tundo; Saidah, Andi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
Evaluation of student satisfaction with campus facilities is one important aspect in improving the quality of college services and infrastructure. However, this satisfaction evaluation process has a gap between student expectations of the facilities provided by the campus. This research aims to design a Decision Support System (DSS) that can help the campus in assessing student satisfaction levels using the Simple Additive Weighting (SAW) method. This method was chosen because of its ability to conduct an assessment based on criteria that have certain weights so as to produce the best alternative ranking. The criteria used in this study include cleanliness, maintenance, comfort, completeness, condition, service, and level of satisfaction. Data was obtained through questionnaires distributed to students in various study programs, focusing on various aspects of campus facilities such as classrooms, laboratories, libraries, hall areas, and podcast studios. It was then processed using SAW steps, including matrix normalization and final score calculation. The result showed that the final results of the evaluation of student satisfaction with campus facilitiesf from 100 respodents obtained a fairly high score of 44 which was said to be quite good. This SAW method is able to provide a clear ranking of the level of student satisfaction, as well as identify areas that require improvement or enchancement at the college.